Cure kinetics of poly (5-ethylidene-2-norbornene) with 2nd generation Hoveyda-Grubbs' catalyst for self-healing applications. (26th September 2018) - Zamal, Hasna Hena; Barba, David; Aissa, Brahim; Haddad, Emile; Rosei, Federico
Abstract: Self-healing polymer composites based on ring-opening metathesis polymerization (ROMP) incorporating second generation Hoveyda-Grubbs' (HG2) catalyst as polymerization initiator and 5-ethylidene-2-norbornene (5E2N) as healing monomer are promising for self-healing applications. This is particularly true at low temperatures that may persist in the internal environment of an operating space vehicle. By using a systematic micro-Raman spectroscopic analysis and a detailed methodology specifically implemented for the investigation of 5E2N and HG2 reactants, we studied the progression of the ROMP reaction over time from room temperature down to −30 °C. The analysis is based on measuring the changes in peak intensity and integrated area of Raman phonons related to the characteristic (CC) functional groups indicating the progression of the reaction with time. The cure kinetic reaction of the 5E2N/HG2 system at low temperatures is found to follow an Arrhenius behavior showing the temperature dependence of the reaction rates. On this basis, the activation energy of the reaction is measured to be 64 (±3) kJ mol −1 (0.663 eV), a value that is about 40% higher than the data reported for similar materials. Graphical abstract: Image 1 Highlights: Polymerization kinetics of 5E2N initiated by Hoveyda-Grubbs' catalyst for low temperatures self-healing applications. In situ monitoring and analysis of the reaction from room temperature down to −30 °C using micro-Raman spectroscopy. The reaction at low temperaturesfollows an Arrhenius behavior showing the temperature dependence of the reaction rates. The activation energy of the reaction is measured to be 64 (±3) kJ.mol −1 (0.663 eV).